Inovasi Kurikulum Pendidikan Islam: Menjawab Tantangan Globalisasi dan Krisis Nilai - Misbahul Arifin; Ramzatul Widad Rizqiyani (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This study focuses on curriculum innovation in Islamic education in response to the challenges of globalization and the value crisis affecting contemporary Muslim societies. The primary objective of this research is to identify and analyze how Islamic schools, particularly Madrasah Diniyah Nurul Jadid, develop and implement a curriculum that is adaptive to global changes while remaining rooted in Islamic values. This study employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using Miles and Huberman’s interactive model. The findings reveal that curriculum innovation is carried out through the integration of Islamic values and 21st-century global competencies such as digital literacy, collaboration, and problem-solving. These innovations encompass structural, pedagogical, and ideological reforms tailored to the unique characteristics of pesantren institutions. However, the implementation still faces challenges related to the readiness of human resources and tensions between innovation and the preservation of traditional values. The implications of this research highlight the importance of a contextual and participatory curriculum approach to strengthen the role of Islamic education as a transformative agent of values in the global era.